Predictors of costs from the hospital perspective of primary pulmonary embolism. Issue 1 (22nd October 2015) - Motte, Serge; Mélot, Christian; Di Pierdomenico, Lionel; Martins, Dimitri; Leclercq, Pol; Pirson, Magali
The objective of this study was to estimate the total hospital cost per patient admitted through the emergency department with a primary diagnosis of pulmonary embolism (PE), and to identify the main components and predictors of costs. Actual costs of care of 652 consecutive patients hospitalised in 10 general hospitals in Belgium, including 31 outlier patients in terms of length of stay (4.8%), were obtained by aggregating all cost components contributing to care of each patient. In both inlier and outlier patients, the mean total cost per patient increased linearly with the degree of severity of illness classes related to the All Patient Refined Diagnosis Related Group (p<0.0001). Medical procedures, nursing activities and hospitalisation accommodation were the main cost components. We identified six independent predictors of costs in inliers: age group, chronic pulmonary heart disease, heart failure, admission to intensive care unit, initial thrombolysis treatment and type of hospital. There was a statistically significant linear trend between age groups and costs (p<0.0001). An increasing burden of comorbid illness was strongly associated with increasing actual cost for caring hospitalised patients for PE. Increasing age was associated with an increase in all main cost components. Increased burden of comorbid illness is associated with increased cost of care for pulmonary embolism patients http://ow.ly/RSTPY